Civil engineering and architecture - Matteson, Donna (Clifton Park, NY : Delmar Cengage Learning, 2012)
Introduction to civil engineering and architecture; Research and design; Location, location, location; Planning for occupancy; Structural design: Building for tomorrow; Mechanicals: The building comes alive; Curb appeal.
Includes index.
Keywords: Civil engineering -- Popular works; Architecture